Overview of Anxiety and Coping Methods of High School Students Facing State University Selection - Hadi, Addini Nurilma; Abidin, Zaenal (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Anxiety is an unpleasant emotional condition for a person that includes subjective fear to physical discomfort. This discomfort will certainly make a person's activities or daily life disrupted. If anxiety disorders are experienced by high school students who will face college entrance selection, it can have an impact on decreasing interest in learning to feelings of insecurity which will have an impact on the quality of learning in preparing for college selection. This study is a descriptive qualitative research that aims to obtain an overview of anxiety in students who face college selection and coping what is done to overcome this anxiety. The participants involved in this study are three adolescents aged 17-18 years who in 2023 are undergoing a college selection process. The purposive sampling method was used to select participants based on their consent and willingness to take part in the study. This research was conducted in May 2023 using an online interview method. Some of the things that triggered anxiety in the study participants included feelings of insecurity in their own abilities, lack of support from those around them, and also feelings of worry about failure and even insufficient economic factors. Even so, participants still have to face the selection to enter state universities so that they can implement several coping mechanisms so that they can focus on studying for the selection exam. Kecemasan merupakan suatu kondisi emosi yang tidak menyenangkan bagi seseorang yang meliputi ketakutan subjektif hingga ketidaknyamanan fisik. Ketidaknyamanan ini tentunya akan membuat aktivitas atau keseharian seseorang menjadi terganggu. Bila gangguan kecemasan dialami oleh siswa SMA yang akan menghadapi seleksi masuk perguruan tinggi, maka dapat berdampak pada menurunnya minat belajar hingga perasaan tidak aman yang akan berdampak pada kualitas pembelajaran dalam mempersiapkan seleksi perguruan tinggi. Penelitian ini merupakan penelitian kualitatif deskriptif yang bertujuan untuk memperoleh gambaran kecemasan pada siswa yang menghadapi seleksi perguruan tinggi serta coping apa yang dilakukan dalam mengatasi kecemasan tersebut. Partisipan yang terlibat dalam penelitian ini adalah tiga orang remaja berusia 17-18 tahun yang pada tahun 2023 sedang menjalani proses seleksi perguruan tinggi. Metode purposive sampling digunakan untuk memilih partisipan berdasarkan persetujuan dan kesediaan untuk mengambil bagian dalam penelitian. Penelitian ini dilakukan pada bulan Mei 2023 dengan metode wawancara online. Beberapa hal yang menjadi pemicu kecemasan pada peserta penelitian antara lain perasaan tidak yakin dengan kemampuan diri sendiri, kurangnya dukungan dari orang sekitar, dan juga perasaan khawatir akan kegagalan bahkan faktor ekonomi yang tidak mencukupi. Meski begitu, peserta tetap harus menghadapi seleksi masuk perguruan tinggi negeri sehingga menerapkan beberapa mekanisme coping agar bisa fokus belajar untuk ujian seleksi tersebut.